Multi-agent system-based polymorphic distributed energy management for ships entering and leaving ports considering computing power resources - Qihe Shan; Qi Qu; Jing Song; Fei Teng; Geyang Xiao; Xin Zhang; Tieshan Li (Complex & Intelligent Systems, 2023)
Abstract In order to realize the intelligent energy management of the complex ship energy system, achieve the carbon peaking and carbon neutrality goal and reduce the ship carbon emissions and ship operating costs, this paper proposes a distributed energy management method for ships entering and leaving ports based on polymorphic network considering computing power resources. Firstly, a polymorphic network-based energy management system for ships entering and leaving ports is proposed to enhance the information exchange between ship computing power, power and port power, simultaneously improve the communication quality and communication security among different modes. Secondly, in order to reduce the ship operating costs and port carbon emissions, the energy management model of ships entering and leaving ports is constructed considering computing power resources. Then, according to the ship’s berthing and departing operation modes, this paper uses the distributed algorithm to solve the energy management problem, and explores the impact on the ship microgrid when the ship’s data load changes. Finally, simulation results verify the effectiveness of the proposed algorithm.